Disorder-specific versus transdiagnostic and clinician-guided versus self-guided internet-delivered treatment for panic disorder and comorbid disorders: A randomized controlled trial. (April 2016) - Fogliati, V.J.; Dear, B.F.; Staples, L.G.; Terides, M.D.; Sheehan, J.; Johnston, L.; Kayrouz, R.; Dear, R.; McEvoy, P.M.; Titov, N.
Highlights: Study compared disorder-specific and transdiagnostic treatment approaches. Study also compared clinician-guided and self-guided treatment approaches. Study is 1 of 4 related randomized controlled trials examining these issues. Study focused on Panic Disorder and comorbid disorders. No marked differences were observed between the treatment approaches. Abstract: Transdiagnostic cognitive behaviour therapy (TD-CBT) aims to target the symptoms of multiple disorders whereas disorder-specific CBT (DS-CBT) targets the symptoms of principal disorders. This study compared the relative benefits of internet-delivered TD-CBT and DS-CBT when provided in clinician-guided (CG-CBT) and self-guided (SG-CBT) formats for people with a principal diagnosis of Panic Disorder (PD). Participants (n = 145) were randomly allocated to receive TD-CBT or DS-CBT and CG-CBT or SG-CBT. Large reductions in symptoms of PD (Cohen's d ≥ 0.71; avg. reduction ≥ 36%) and moderate-to-large reductions in symptoms of comorbid depression (Cohen's d ≥ 0.71; avg. reduction ≥ 33%), generalised anxiety disorder (Cohen's d ≥ 0.91; avg. reduction ≥ 34%) and social anxiety disorder (Cohen's d ≥ 0.50; avg. reduction ≥ 15%) were found over the 24-month follow-up period. Highlighting their efficacy and acceptability, no marked and consistent differences were observed between TD-CBT and DS-CBT or CG-CBT and DS-CBT.